SEED DEPOSITION BY BIRDS ON ARTIFICIAL PERCHES AT DIFFERENT DISTANCES FROM A GALLERY FOREST IN THE CERRADO AREA - Oliveira, Ademir Kleber Morbeck; Bocchese, Ricardo Anghinoni; Pereira, Kátia Raulickis Fortes; Carvalho, Thiago Dutra (Floresta, 2018)
The objective of this study was to evaluate the deposition of seeds under artificial perches located at different distances from a gallery forest in the Cerrado area in the city of Campo Grande, state of Mato Grosso do Sul, Brazil. The experiment was carried out at the Fazenda Escola Três Barras where 20 crude eucalyptus artificial perches were deployed at distances of 10, 20, 40 and 80 meters from the edge of a 400 meter long forest. Data collection was performed every two weeks for a period of one year. A bird survey was carried out at the same time and a total of 190 hours of direct observation were made. Overall, 21,283 seeds were collected beneath the perches; these came from 27 plant species, with the most abundant representation from the pioneer tree species Cecropia pachystachya, Miconia elegans and Myrsine coriacea (93.31% of total seeds). The survey of birds identified 77 species, with a predominance of insectivorous and omnivorous types. The results indicated that perches installed at the greatest distance from the forest area yielded a lower seed deposition rate, demonstrating that distance determines the effectiveness of the artificial perches, although they are still able to attract some bird species. The results of the experiment demonstrated that use of artificial perches is an effective method to promote the deposition of seeds in areas without tree vegetation, favoring the creation of a seed bank.